THE EFFECT OF PRICE DISCOUNTS, STORE ATMOSPHERE AND VISUAL MERCHANDISING ON IMPULSE BUYING - Putu Rara Puspita; Gede Bayu Rahanatha (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study aims to determine the effect of price discount, store atmosphere, and visual merchandising on impulse buying behavior of Transmart retail consumers in Denpasar. Stimulus-Response Theory is used in this study. The method of determining the sample in this study is non probability sampling using purposive sampling technique in a total of 112 respondents. The data were gathered through distributing research questionnaires to respondents. The analysis was conducted using statistic descriptive analysis and statistic inferential analysis that includes multiple linear regression analysis, classical assumption test, F- test and t-test. The result showed that price discount has a positive and significant effect on impulse buying; store atmosphere has a positive and significant effect on impulse buying; visual merchandising has a positive and significant effect on impulse buying; and those variables were simultaneously affecting the impulse buying behavior. The implication of this study suggests that price discount, store atmosphere, and visual merchandising can be considered as stimuli to increase impulse buying on Transmart retail consumers in Denpasar.